Lytic Activity of Bacterial Chitinases in aspergillus flavus Link ex Fries and A parasiticus Speare - Mozar-doyungan, Stella Marie; F. Dalmacio, Ida (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The mycolyte activity of the crude chitinases obtained two strains of Bacillus circulans (5Bc and 7Bc), two strains of Serratin marcescens (11Sm and 14Sm), Arthrobacter Inteus(6AI) and Streptomyees grisens (9sg) was evaluated against two species of aflatoxigenic fungi, Aspergillus flavus and A, parasiticus, Lysis was confirmed based on the presence of N-aceylalcasamine (CleNAe), « product of chitin degradation, in a reaction mixture containing hyphas as substrate for chitinase activit. Acroscopie examination of the mycelia treated with crude chitinase enzymes showed restricted mycelial growth. All the undiluted crude enzymes cauxed significant reduction in the mean diameter of fungal colonies in PDA 24 hours after Treatment,